Prevalence study of cholinesterase inhibition among RKPBV staff in Negeri Sembilan, 1996 - Ismail Salleh,; Jamal Hisham Hashim, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study was done to detect the inhibition of plasma cholinesterase among 119 males RKPBV staff in Negeri Sembilan in February and March 1996. The respondents included 59 sprayers and 60 nonsprayers. The objective of the study is to detect the level of exposure to pesticide among the RKPBV staffs by means of self admi1ustered questionnaire, blood test for plasma cholinesterase level and ECG. It also investigates the influence of sociodemography, job status, knowledge, attitude and practice, frequency of spraying, knowledge of pesticide poisoning symptoms on plasma cholinesterase level The result of the study shows that the mean cholinesterase level among sprayers are (5390.17 ± 1019.19) lower than nonsprayers (5492 ± 1242.66 u/l). However the difference is not statistically significant. It also shows abnormal ECG readings among 15 of the respondents. This indicate that there exist a certain level of cholinesterase inhibition among those exposed to pesticide. There is no significant association between cholinesterase level with length of service, frequency of spraying, practice attitude, knowledge and 'symptoms of pesticide poisoning. Preventive measure as well as periodic medical examination can help to reduce the health hazard due to pesticide exposure.